Impact of seed mycoflora of soybean on seed quality: Impact of seed mycoflora of soybean on seed quality - RAJESHWARI M C; RAVI HUNJE (Journal of Oilseeds Research, 2020)
The seeds collected from major soybean growing areas of northern Karnataka were tested for the association of mycoflora and seed quality parameters. The mycoflora associated with soybean were Colletotrichum truncatum, Cercospora kikuchii, Fusarium oxysporum, Rhizoctonia solani, Rhizopus stolonifer and saprophytic fungiare Aspergillus flavus, Aspergillus niger and Penicillium spp. Alternaria spp., Cercospora kikuchii, Fusarium spp., Penicillium spp. led to deterioration and germination failure of soybean seeds. The seeds collected from Bidar region recorded high seed quality parameters.